A Survey on Image-Based Rendering - Representation, Sampling and Compression - Zhang, Cha; Chen, T. (Signal Processing: Image Communication, 2004)
Image-based rendering (IBR) has attracted a lot of research interest recently. In this paper, we survey the various techniques developed for IBR, including representation, sampling and compression. The goal is to provide an overview of research for IBR in a complete and systematic manner. We observe that essentially all the IBR representations are derived from the plenoptic function, which is seven dimensional and difficult to handle. We classify various IBR representations into two categories based on how the plenoptic function is simplified, namely restraining the viewing space and introducing source descriptions. In the former category, we summarize six common assumptions that were often made in various approaches and discuss how the dimension of the plenoptic function can be reduced based on these assumptions. In the latter category, we further categorize the methods based on what kind of source description was introduced, such as scene geometry, texture map or reflection model. Sampling and compression are also discussed respectively for both categories.